2021
DOI: 10.1007/s00395-021-00853-z
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of a gene-edited mouse model to gain insights into the disease mechanisms of a titin missense variant

Abstract: Titin truncating variants are a well-established cause of cardiomyopathy; however, the role of titin missense variants is less well understood. Here we describe the generation of a mouse model to investigate the underlying disease mechanism of a previously reported titin A178D missense variant identified in a family with non-compaction and dilated cardiomyopathy. Heterozygous and homozygous mice carrying the titin A178D missense variant were characterised in vivo by echocardiography. Heterozygous mice had no d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…HSPA8 (Hsc-70) is reported to be a titin interacting protein in an LVNC gene-edited mice model. Therefore, this gene could have a critical role in pathogenesis ( 32 ). Trophinin associated protein (TROAP) is shown to be involved in myocardial infarction ( 33 ), thus, its role in LVNC could also be important.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HSPA8 (Hsc-70) is reported to be a titin interacting protein in an LVNC gene-edited mice model. Therefore, this gene could have a critical role in pathogenesis ( 32 ). Trophinin associated protein (TROAP) is shown to be involved in myocardial infarction ( 33 ), thus, its role in LVNC could also be important.…”
Section: Resultsmentioning
confidence: 99%
“…However, the roles of these pathways have not been extensively studied in relation to the development of LVNC ( 27 , 28 ). Furthermore, GSEA analysis identified HSPA1, DMD, and ADCY1 as having significant relevance in developing heart ailments and which presumably play a critical role in developing LVNC ( 32 , 34 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…A potential post-translational mechanism for the reduced telethonin expression level in the hearts of HOM mice is a greater susceptibility of non-phosphorylated telethonin protein to degradation by intracellular pathways. Previous studies indicate that telethonin protein is subject to degradation by the UPS in multiple cell models ( Heng et al, 2008 ; Polge et al, 2018 ; Jiang et al, 2021 ). To explore the potential role of the UPS system in regulating telethonin protein expression level in the presence and absence of phosphorylation at S157/S161, we determined the effects of the UPS inhibitor MG132 ( Rock et al, 1994 ) in ventricular myocytes that were isolated from the hearts of WT and HOM mice and maintained in short-term culture.…”
Section: Resultsmentioning
confidence: 99%
“…Proteasome inhibition has also been shown to inhibit MDM2-mediated degradation of telethonin in H1299 cells ( Tian et al, 2006 ). Furthermore, a recent study has identified telethonin as a target of the proteasome in a titin missense variant mouse model of cardiomyopathy, where degradation of unbound, cytoplasmic telethonin by the proteasome results in proteasomal overload ( Jiang et al, 2021 ). In line with these observations, our study has identified UPS as an important post-translational mechanism responsible for the reduced telethonin expression level in the HOM mice; the proteasome inhibitor MG132 was found to increase significantly the expression level of S157/161A telethonin protein in myocytes from HOM mice, but not the expression level of phosphorylatable telethonin protein in myocytes from WT mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation